Do European Funds Contribute to the Sustainable Development of Romania? - Gabriela-Diana Baraghin; Ioana Beleiu (Ovidius University Annals: Economic Sciences Series, 2022)
The social, economic well-being and the sustainability of the planet are European strategic goals that characterize a good standard of living, but often, a successful economy depletes natural resources far beyond limits. The European Union is achieving its objectives by providing European non-reimbursable funds to the member states, thus enabling the development of those states to reduce regional inequalities. The economic growth is an important factor in the economic development of a country, several factors being able to favour this growth, and which can be measured through the gross product per capita. This study focuses on the sustainable development of Romania by measuring two relevant indicators, gross product per capita and the Happy Planet Index in relation to the value of the funds absorbed per capita. This study also identifies the trend line of the correlation between the aforementioned indices and established the intensity through the Pearson correlation coefficient.